Virtual Dating and the COVID-19 Pandemic: Investigating Motives, Predictors, and Outcomes - Youngvorst, Luke; Pham, Thao (Human Communication & Technology, 2023)
The COVID-19 pandemic altered myriad aspects of social and cultural life, with impacts continuing to ripple across the globe. The present study provides empirical insight into virtual dating following the COVID-19 pandemic, exploring motives (i.e., gratifications), predictors (i.e., age; sex; sexual orientation; living situation; vaccination status), and outcomes (i.e., loneliness). Participants (N = 393) were recruited from Amazon's Mechanical Turk (MTurk) in March 2021, approximately one year after initial shelter-in-place and lockdown orders went into effect. Results revealed that demographic and situational factors were significantly related to virtual dating motives. Additionally, several virtual dating motives were significantly associated with loneliness. Implications are discussed regarding the landscape of virtual dating following the COVID-19 pandemic.